A large-scale marine protected area for the sea of Rapa Nui: From ocean grabbing to legitimacy. (1st December 2020) - Aburto, Jaime A.; Gaymer, Carlos F.; Govan, Hugh
Abstract: The last decade has seen a noticeable advance in ocean protection through the creation of several LSMPAs which are largely driven by Aichi Target 11 under CBD. This paper uses the "Ocean grabbing framework" to assess the process preceding the announcement of a LSMPA in Rapa Nui, its rejection, the reformulation of the process and the ultimately successful establishment of a Multiple Uses Marine Protected Area (MUMPA). The assessment focused on: a) the quality of governance, b) the effects on livelihoods and human security, and 3) the potentially interlinked social and ecological impacts. The rejection of the initial LSMPA process was associated with lack of transparency, inadequate participatory processes, and lack of accountable decision-making all of which could have had adverse social and ecological outcomes and turned the LSMPA into an "ocean grab". Factors that contributed were associated to inappropriate use of financing, political lobbying and pressure exerted by a NGO that tried to deploy its agenda disconnected from local indigenous interests. In a major turning point stemming from the vigorous local rejection of the initial LSMPA, a bottom-up process led by a local institution (CODEIPA) and other Rapanui organizations, coordinated with the Chilean Government, resulted in an unprecedented participatory process ending in the creation of the largest MPA in the Americas, that will be comanaged by Rapanui people and the Chilean Government. It is hoped that the results of this analysis can contribute to the development of good practices in marine conservation worldwide, maximizing marine conservation outcomes and avoiding undesirable social and ecological impacts. Graphical abstract: Image 1 Highlights: Ocean grabbing (OG) was detected in the process to create a LSMPA in Rapa Nui. Main OG issues were lack of transparency and inadequate participatory process. To reverse initial OG a participatory process was run by the Rapanui and the Chilean Government. A Multiple Uses MPA was approved by Rapanui after consultation and voting. The MUMPA will be co-managed by a Sea Council with Rapanui majority.